2007
DOI: 10.1063/1.2748101
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanisms of amorphous SiOx nanowires

Abstract: Growth of β -SiC nanowires and thin films by metalorganic chemical vapor deposition using dichloromethylvinylsilane J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
4
33
0
Order By: Relevance
“…The Si L 1 edge is about 160 eV [36]. According to the reference EELS spectrum of SiO x [37], the nanowire can be verified as amorphous SiO x . To further determine the ratio of Si and O in SiO x nanowires, EDS was employed and an example was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Si L 1 edge is about 160 eV [36]. According to the reference EELS spectrum of SiO x [37], the nanowire can be verified as amorphous SiO x . To further determine the ratio of Si and O in SiO x nanowires, EDS was employed and an example was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, at the annealing temperature of 1100 C, the smaller Au-Si droplets move laterally along the SiO x /Si interface, due to the synergistic effect of difference of the SiO x /Si interface tension on opposite sides of a droplet and the thermal fluctuation. It should be noted that this study confirmed the formation of SiO x surface islands during annealing Au thin-films at elevated temperature, and these surface islands may be easily misinterpreted as Au nanoparticles, 16 so that caution is needed to explain the formation of such surface islands. Since Au has been commonly used to induce semiconductor nanowires, this study provides insight of how the Au is behaved, which is critical for understanding the growth of semiconductor nanowires.…”
mentioning
confidence: 79%
“…A continuous supply of both Si and oxygen sources would then provide the feedstock needed for the silica nanowire growth. 2) The PL measurement result in Fig. 4 indicates that our nanowires are silica nanowires rather than SiGe oxide nanowires.…”
Section: Discussionmentioning
confidence: 99%
“…1) Interest in this latter application has been fuelled by the discovery of stable and strong blue light emission from silica nanowires. 1) Intensive research has been carried out on the growth of silica nanowires using techniques such as pulsed laser ablation, 2) catalytic chemical vapor deposition (CVD), 3) and carbothermal reduction. 4) At the same time, the growth mechanism has been investigated and several growth models have been proposed, such as the vapor-liquid-solid (VLS) model, 1,5) the vapor-solid (VS) model, 6) and the solid-liquid-solid (SLS) model.…”
Section: Introductionmentioning
confidence: 99%